Pengaruh Model Discovery Learning terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Redoks Peserta Didik SMAN 2 Buru - Dahlan, Rosmidah Rezki; Sugiarti, Sugiarti; Hasri, Hasri (Program Pasca Sarjana UNM, 2023)
This experimental research aims to examine the influence of Discovery Learning Model on critical thinking skills and redox learning outcomes. The research design used was Posttest-Only Control Design and obtained students of grade X MIA 1 cconsisted of 25 people as the experimental class and grade X MIA 2 consisted of 29 people as the control class. The data analysis techniques used were descriptive and inferential statistical analysis. The results of the study reveal that learning using the Discovery Learning Model obtains the value of critical thinking skills are 79%. The cognitive learning outcomes are 83%, affective learning outcomes are 83%, and psychomotor learning outcomes are 80%, which is higher than conventional learning. Thus, they have a significant influence based on hypothesis testing on learning outcomes and critical thinking skills with the value of Sig. (2- tailed) < 0.05. In addition, the results of critical thinking skills have a correlation with learning outcomes with Pearson correlation values of 0.853, 0.811, and 0.652, outcomes is at a very high and sufficient level of closeness. Therefore, the conclusion of the study is the use of Discovery Learning Model influences critical thinking skills and redox learning outcomes.